Bulk Enthalpy of Melting of Poly (l‐lactic acid) (PLLA) Determined by Fast Scanning Chip Calorimetry. Issue 11 (11th April 2022) - Jariyavidyanont, Katalee; Du, Mengxue; Yu, Qiang; Thurn‐Albrecht, Thomas; Schick, Christoph; Androsch, René
Abstract: The bulk enthalpy of melting of α ‐crystals of poly (L‐lactic acid) (PLLA) is evaluated by fast scanning calorimetry (FSC), by correlating the melting enthalpy of samples of different crystallinity with the corresponding heat capacity at 90 °C, that is at a temperature higher than the glass transition temperature of the bulk amorphous phase and lower than the melting temperature. Extrapolation of this relationship for crystals formed at 140 °C towards the heat capacity of fully solid PLLA yields a value of 104.5±6 J g −1 when melting occurs at 180–200 °C. The analysis relies on a two‐phase structure, that is, absence of a vitrified rigid amorphous fraction (RAF) at the temperature of analysis the solid fraction (90 °C). Formation and vitrification of an RAF are suppressed by avoiding continuation of primary crystallization and secondary crystallization during cooling the system from the crystallization temperature of 140 °C to 90 °C, making use of the high cooling capacity of FSC. Small‐angle X‐ray scattering (SAXS) confirmed thickening of initially grown lamellae which only is possible if these lamellae are not surrounded by a glassy RAF. Linear crystallinity values obtained by SAXS and calorimetrically determined enthalpy‐based crystallinities agree close to each other. Abstract : A specific route of crystallization of poly (L‐lactic acid) (PLLA) assures absence of a vitrified rigid amorphous fraction, which permits correlating the heat capacity slightly above the glass transition temperature, yielding the crystal fraction, and the enthalpy of melting. This correlation allows a straightforward re‐evaluation of the bulk enthalpy of melting of α ‐crystals of PLLA.